Characteristics of the Occurrence of Ion Upflow in Association With Ion/Electron Heating in the Polar Ionosphere. Issue 7 (22nd July 2019) - Ji, Eun‐Young; Jee, Geonhwa; Lee, Changsup
Abstract: We investigate the statistical characteristics of the ion upflow occurrence in association with ion and electron heatings in the polar ionosphere using the European Incoherent Scatter Svalbard Radar during the period of 2000–2015. The ion upflow events are classified as four types: with ion temperature increase (Type 1), with electron temperature increase (Type 2), with both ion and electron temperature increases (Type 3), and without any temperature increase (Type 4). These four types of upflow events are statistically analyzed with various geophysical conditions. We found that the overall occurrence of ion upflow is highest for Type 3 and then followed by Type 2, Type 1, and Type 4. This result indicates that the ion upflow is highly associated with soft particle precipitation induced electron heating, which becomes more effective with simultaneous friction induced ion heating. The statistical characteristics of ion upflow is summarized as follows: (1) It is most highly distributed in the daytime with a double peak structure but a deep minimum at dusk, (2) the highest occurrence appears at about 350‐ to 450‐km altitude for most of local time but extended to higher altitude near the magnetic local noon, (3) the ions mostly reach only up to about 200 km above their initiated altitudes, (4) it tends to increase with magnetic activity, particularly during the daytime, but (5) decreases and distributed at higher altitude with increasing solar activity, and (6) finally, the maximum occurrence appears in December solstice but the minimum in June solstice for most of local times. Key Points: Ambipolar electric field with electron heating may be more effective to produce ion upflow when the ions are also simultaneously heated Diurnal variation of ion upflow occurrence shows a double peak structure during the day and a deep minimum at dusk Maximum occurrence appears in December solstice but minimum in June solstice